Selection of Yeasts as Starter Cultures for Table Olives: A Step-by-Step Procedure - Bevilacqua, Antonio; Corbo, Maria Rosaria; Sinigaglia, Milena (Frontiers in Microbiology, 2012)
In the past yeasts were traditionally regarded as the spoiling microorganisms for table olives; however, their role and impact for product quality and for the correct course of fermentation has been revised and nowadays many authors suggest a controlled inoculum of yeasts both in alkali-treated and untreated olives. The selection of a starter is a complex process, involving different steps. After strain isolation from raw material, the first step is the identification through phenotyping and genotypic methods; then, isolates should be characterized to assess their GRAS (generally recognized as safe) status and technological properties (growth with salt added, at various temperatures and pHs, pectolytic and xylanolytic activity, lipolytic activity, resistance to some preservatives, functional impact). After studying these properties, the results can be submitted to data analysis (many times a statistical multivariate approach) and strain selection. The number of strains to be selected depends on several factors, above all on the main goal: obtaining a single or a multiple-strain starter. After this step, starter should be used for a pilot fermentation on a lab scale, highlighting its performances, limits and benefits, as well as all the issues related to its production, storage and stability throughout the time. Finally, starter optimization conducted on a lab scale should be verified on real conditions.